2016
DOI: 10.1155/2016/4156456
|View full text |Cite
|
Sign up to set email alerts
|

A Fusion Protein Consisting of the Vaccine Adjuvant Monophosphoryl Lipid A and the Allergen Ovalbumin Boosts Allergen-Specific Th1, Th2, and Th17 ResponsesIn Vitro

Abstract: Background. The detoxified TLR4-ligand Monophosphoryl Lipid A (MPLA) is the first approved TLR-agonist used as adjuvant in licensed vaccines but has not yet been explored as part of conjugated vaccines. Objective. To investigate the immune-modulating properties of a fusion protein consisting of MPLA and Ovalbumin (MPLA : Ova). Results. MPLA and Ova were chemically coupled by stable carbamate linkage. MPLA : Ova was highly pure without detectable product-related impurities by either noncoupled MPLA or Ova. Ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…In agreement with our results, Schülke and colleagues showed that, as compared to its parent molecule LPS, MPLA induced a qualitatively similar but significantly less potent pro-inflammatory immune response in in vitro, ex vivo , and in vivo human and mouse test systems22. They further successfully generated a novel fusion protein consisting of MPLA and a model allergen Ovalbumin (MPLA : Ova), and demonstrated that MPLA : Ova can boost Th1, Th2, and Th17 TC-derived cytokine secretion and hence induce both stronger innate and adaptive immune responses compared to the mixture of both components23. Based on experimental evidence, Chilton and colleagues have postulated that LPS and native diphosphoryl lipid A potently induce NLRP3 expression resulting in increased NLRP3 protein production and effective inflammasome assembly whereas weak NLRP3 induction, as seen after MPLA exposure, fails to elicit adequate NLRP3 protein production2425.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our results, Schülke and colleagues showed that, as compared to its parent molecule LPS, MPLA induced a qualitatively similar but significantly less potent pro-inflammatory immune response in in vitro, ex vivo , and in vivo human and mouse test systems22. They further successfully generated a novel fusion protein consisting of MPLA and a model allergen Ovalbumin (MPLA : Ova), and demonstrated that MPLA : Ova can boost Th1, Th2, and Th17 TC-derived cytokine secretion and hence induce both stronger innate and adaptive immune responses compared to the mixture of both components23. Based on experimental evidence, Chilton and colleagues have postulated that LPS and native diphosphoryl lipid A potently induce NLRP3 expression resulting in increased NLRP3 protein production and effective inflammasome assembly whereas weak NLRP3 induction, as seen after MPLA exposure, fails to elicit adequate NLRP3 protein production2425.…”
Section: Discussionmentioning
confidence: 99%
“…The alum-toxofilin group increased IgG1 levels compared with non-adjuvanted toxofilin, skewing the immune response towards a Th2 response associated with strong production of the IL-4, IL-10, and the IgG1 antibody subtype. Conversely, the MPLA adjuvant is known to induce a Th1-biased immune response [32], resulting in significantly increased specific serum IgG2a isotype antibodies and higher levels of Th1 cytokines. Importantly, the alum-MPLA-toxofilin could effectively lead to a shift from a Th2-skewed immune response towards a Th1 profile and, ultimately, to a balanced immune response compared with the use of a single adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…The detoxified TLR-4 ligand, 3- O -deacyl-4′-monophosphoryl lipid A (MPLA), is a lipopolysaccharide (LPS)-derived, heterogeneous blend of varying length MPL molecules from Salmonella minnesota R595 . The MPLA extraction and treatment procedure resulted in three distinct modifications compared to the parent molecule: (1) the removal of the core polysaccharide containing the O-antigen, (2) the removal of one phosphate group, and (3) one fatty acid chain ( 116 , 117 ). MPLA has been shown to promote T H 1 immune responses and to have a favorable safety profile when compared to LPS ( 118 120 ).…”
Section: Strategies To Increase Immunogenicity Of Nano-vaccinesmentioning
confidence: 99%